Students’ Perspectives on Learning Science Education Amidst Covid-19 - Ghimire, Rajan; Gurung, Gem Prasad (The Journal of Aadikavi, 2023)
One of the diseases caused by a Corona virus shook the whole world. This situation challenged the education system across the world and compelled educators to shift to an online mode of teaching. Many academic institutions that were persistent to keep their traditional pedagogical approach were also forced to change their teaching methods. This study aims to assess science education students’ experiences and perceptions on this global issue especially on science teaching and learning process. The studies are based on qualitative research and through in-depth interviews with respondents and data are analyzed. The online distance teaching and learning process tries to address to some extent the needs of students who cannot or do not want to participate in traditional classroom settings. But there are some challenges for the students and teachers for the science teaching learning process. This study focuses on learning difficulties during pandemics and gives insightful feedback to planners and policy makers.